Chemical Composition and Petrogenetic Implications of Apatite in the Khibiny Apatite-Nepheline Deposits (Kola Peninsula) - Lia Kogarko (Minerals, 2018)
Khibiny, one of the largest of the world’s peralkaline intrusions, hosts gigantic apatite deposits. Apatite is represented by F-apatite and it contains exceptionally high concentration of SrO. (4.5 wt % on average) and increased amounts of rare earth elements (REEs; up to 8891 ppm). Such enrichment of apatite ores in REEs defined Khibiny deposit as world-class deposit with resources reaching several millions tons REE2O3. Apatite from the Khibina alkaline complex is characterized by the significant enrichment in light REEs relative to the heavy REEs (with average Ce/Yb ratio of 682) and the absence of a negative Eu anomaly. The obtained geochemical signature of apatite suggests a residual character of the Khibiny alkaline magma and it indicates that the differentiation of the primary olivine-melanephelinitic magma developed without fractionation of plagioclase which is the main mineral-concentrator of Sr and Eu in basaltic magmatic systems. The compositional evolution of the Khibiny apatite in the vertical section of the intrusion reflects primary fractionation processes in the alkaline magma that differentiated in situ. The main mechanism for the formation of the apatite-nepheline deposits was the gravitational settling of large nepheline crystals in the lower part of the magma chamber, while very small apatite crystals were suspended in a convective magma, and, together with the melt, were concentrated in its upper part of the magmatic chamber.